GAYA KEPEMIMPINAN PEREMPUAN DI KEMENTERIAN AGAMA - Nurmi, Seno Andri, Noor Efni Salam (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Women's Leadership Style in the Ministry of Religion. This study aims to analyzethe style of women's leadership in the ministry of religion in the city of Pekanbaru. This study usesa qualitative descriptive research method approach. Data collection techniques usingquestionnaires, interviews, and observations. Research informants were the Head of the Ministryof Religion Office. Head of Subdivision, Head of Sharia Organizing Section, and ASN Staff. Dataanalysis in this study used interactive model analysis from Miles and Huberman which included:the stages of data reduction, data presentation, and data verification to draw conclusions. Theresults of the study can be concluded that the leadership of women in the Ministry of Religion inPekanbaru is more dominant using participatory leadership styles. Although the leadershipsometimes leaders combine other leadership styles and also use the theory of situations in theapplication of leading a position.